Synthesis, Characterization and Investigation the Antibacterial Activity of New Heterocyclic Compounds Derived From 4-(4`-methoxy benzoyloxy) benzaldehydethiosemicarbazone - Jamel, Nebras M.; Baker, Rajaa K.; Tomma, Jumbad H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
4-Thiazolidinone were synthesized by three steps,the reaction of ansoyl chloride with 4hydroxy benzaldehyde to give 4-(4`-methoxy benzoyloxy) benzaldehyde[I].The reaction of later compound with thiosemicarbazideled to formation thiosemicarbazon [II] and the reacted thiosemicarbazone with chloro acetic acid in CH3CO2Na medium to yield 4- thiazelidinone compound[III].The 4-thiazolidinone [III]was used as a key intermediates to synthesis new compounds, compound[IV] synthesized from the reaction [III] with acetic anhydride, while the reaction of compound [III] with amines to yield azo compound[V]a,b,c. The azo compound reacted with benzoyl chloride or anisole chloride in basic medium to get a new esters compound[VI]a,b. Also, synthesis oxazepine compound[VII],[VIII] and [IX]a,b,c from heating schiff bases [III],[IV][V]a,b,c with phthalic anhydride in dry benzene in cyclo-addition reaction. The compounds were characterized by FTIR and 1HNMR (of some of them), the synthesized compounds have been screened for their six species of bacteria were used in this study as tested organisms. These are pseudomonas aeruginosa, klebseilla, providencea, Serratiamarcescens(Gram negative) and staphylococcus epidermidis, Bacillus(Gram positive).